Identifying lead users for user-centered design (UCD) in sports product development - Leen, R.; Usma, C.; Antlej, K.; Collins, P. K. (Proceedings, 2018)
There is great benefit for small medium enterprises (SMEs) and startups to utilize lead users in product development. By utilizing lead users companies can make products that are more commercially attractive and better accepted in the market. However, identifying lead users has traditionally been a difficult and expensive task. In the past, lead users have been found through time consuming personal networking, telephone interviews, mail questionnaires and data mining of often large user bases. This paper proposes that identification can be made more efficient by adapting some of these techniques, through taking a digital approach using existing social media communities such as those on Facebook. It is proposed that using social media application programming interfaces (APIs) could allow what used to be reserved for large multinationals, could be made accessible to SMEs and startup companies without extensive resources.